209k views
0 votes
Csc x - csc x cos^2x = sin x verify

User Beeender
by
6.4k points

1 Answer

5 votes

Answer:


  • \csc \left(x\right)-\csc \left(x\right)\cos ^2\left(x\right)=\sin \left(x\right)

Explanation:

Given the expression


csc\:x\:-\:csc\:x\:cos^2x=sin\:x

Let us verify whether the L.H.S is equal to the R.H.S or not


\csc \left(x\right)-\csc \left(x\right)\cos ^2\left(x\right)


\mathrm{Use\:the\:following\:identity}:\quad \cos ^2\left(x\right)=1-\sin ^2\left(x\right)


=\csc \left(x\right)-\left(1-\sin ^2\left(x\right)\right)\csc \left(x\right)


=\csc \left(x\right)-\csc \left(x\right)\left(1-\sin ^2\left(x\right)\right)


=\csc \left(x\right)-\csc \left(x\right)+\sin ^2\left(x\right)\csc \left(x\right)


\mathrm{Add\:similar\:elements:}\:\csc \left(x\right)-\csc \left(x\right)=0


=\sin ^2\left(x\right)\csc \left(x\right)


\mathrm{Use\:the\:following\:identity}:\quad \csc \left(x\right)=(1)/(\sin \left(x\right))


=(1)/(\sin \left(x\right))\sin ^2\left(x\right)


\mathrm{Cancel\:the\:common\:factor:}\:\sin \left(x\right)


=\sin \left(x\right)

Thus,


  • \csc \left(x\right)-\csc \left(x\right)\cos ^2\left(x\right)=\sin \left(x\right)
User Michal Kuklis
by
6.4k points